The Effect of Collaborative Strategic Reading (CSR) on Students' Reading Comprehension of Narrative Text at MTS Sultan Hasanuddin Rangkas Bitung (Universitas Pamulang, 2024)
This study focuses on the effect of teaching reading using collaborative strategic reading. This study uses the Students Team Achievement Division (Group) learning collaboarive strategic . The purpose of this study is to find out whether there is a development of students' reading ability after teachers teach using collaborative strategic. This study uses pre-experimental research. The population used for this study were students of MTS Sultan Hasanuddin located on Jl. Raya Muncang Kp, Pal 4 Jalupang Mulya. Raya Rt 02/ Rw 04, Jalupang Mulya, Lewidamar District, Lebak City, Banten 42362 . The sample in this study were 11 grade 8 students of MTS Sultan Hasanuddin who were heterogeneous because they had different levels of education. Instruments in collecting data using a reading test. The author carried out pre-test and post-test and data analysis using the t-test collaborative stategic reading has improved students' reading abilities in heterogeneous students, especially when the 8th grade students are taught using the strategic collaborative reading.